Vulnerability of Energy Consumers - National Security Issue - Musatescu Virgil (Problems of the Regional Energetics)
Energy providing is a complex problem, which includes both common features for all categories of consumers and particularities, which emerge from the declaration on human rights. As an index of the level of heat using the concept of 'energy poverty'. In counterbalance, this concept proposes the use of the notion of "vulnerability" for these purposes. The concept of "vulnerable consumer" point of view of energy is still defined in the 2012 electricity law in Romania. In this context, the paper examines the vulnerability characteristics indicating meanings on widening energy paradigm by replacing the phrase "energy poverty" by "energy welfare". The paper presents quantitative issues regarding the current situation in Romania with explaining the need treatment paradigm change simplistic approach to the problem of vulnerable consumers, which really is a matter of national security.